Sex Hormone–Dependent Lipid Mediator Formation in Male and Female Mice During Peritonitis - Troisi, Fabiana; Pace, Simona; Jordan, Paul M.; Meyer, Katharina P. L.; Bilancia, Rossella; Ialenti, Armando; Borrelli, Francesca; Rossi, Antonietta; Sautebin, Lidia; Serhan, Charles N.; Werz, Oliver (Frontiers in Pharmacology, 2022)
Introduction: Sex differences are obvious in the incidence and severity of inflammation-related diseases that frequently preponderate in women. Lipid mediators (LMs), mainly produced by lipoxygenase (LOX) and cyclooxygenase (COX) pathways from polyunsaturated fatty acids (PUFA), regulate all stages of inflammation. Experimental and clinical studies revealed sex divergences for selected LM pathways without covering the entire LM spectrum and only few studies have addressed the respective role of sex hormones. Here, we performed comprehensive LM profile analysis with inflammatory peritoneal exudates and plasma from male and female mice in zymosan-induced peritonitis to identify potential sex differences in LM biosynthesis during the inflammatory response. The impact of sex hormones was addressed by employing gonadectomy. Methods: Male and female CD1 mice received intraperitoneal injection of zymosan to induce peritonitis, a well-established experimental model of acute, self-resolving inflammation. Mice were gonadectomized 5 weeks before peritonitis induction. Peritoneal exudates and plasma were taken 4 h (peak of inflammation) and at 24 h (onset of resolution) post zymosan and subjected to UPLC-MS-MS-based LM profiling; exudates were analyzed for LM-biosynthetic proteins by Western blot, plasma was analyzed for cytokines by ELISA. Results: Pro-inflammatory COX and 5-LOX products predominated in the peritoneum of males at 4 and 24 h after zymosan, with slightly higher 12/15-LOX products in males after 24 h. Amounts of COX-2, 5-LOX/FLAP, platelet-type 12-LOX and 15-LOX-1 were similar in exudates of males and females. In plasma of males, only modest elevation of these LM was apparent. At 4 h post zymosan, gonadectomy strongly elevated 12/15-LOX products (e.g., 17-HDHA) in the exudates of males, while in females free PUFA and LOX products were apparently decreased. In plasma, gonadectomy impaired most LM in both sexes at 4 h with rather up-regulatory effects at 24 h. Elevated 15-LOX-1 enzyme was evident in exudates of males at 24 h which was impaired by orchiectomy without striking impact of gonadectomy on other enzymes in both sexes. Conclusions: Our results reveal obvious sex differences and roles of sex hormones in LM-SPM biosynthetic networks in acute self-resolving inflammation in mice, with several preponderances in males that appear under control of androgens.